Corporate strategy response of the big three banks in Singapore. - Ong, Vincent Wee Kiat. (2008)
This study examines the how corporate strategy of the big three Singapore banks, Development Bank of Singapore (DBS), Overseas-Chinese Banking Corporation (OCBC) and United Overseas Bank (UOB), have changed over this period. In addition, the study also uncovers the reasons behind the strategy response.